(untitled) (REMUNOM, 2025)
The present study aimed to verify the effects of osteopathic manipulative treatment in individuals with neck pain in the scientific literature. In this perspective, an integrative review of the literature was carried out between January and February 2025, based on consultations in the Pubmed, Physiotherapy Evidence Database (PEDro) and Trip Medical Database (TRIP DATABASE) databases. Initially, 856 bibliographic references were identified. After applying the eligibility criteria, ten were selected to compose the present review. The studies examined confirmed the effectiveness of osteopathic manipulative therapy (OMT) in relieving chronic neck pain and improving the functionality of individuals. In addition, the combination of OMT with stretching and strengthening exercises proved to be more effective than performing exercises alone in reducing pain and disability. In summary, the studies examined demonstrate the applicability of osteopathic manipulative therapy in the treatment of chronic neck pain.